Common Postoperative Complications Following General Anesthesia in Oral and Maxillofacial Surgery: A Cross-sectional Study - Radha Saodekar; Rajashree Gondhalekar; Jayshree Kalamkar (Academia Anesthesiologica International, 2022)
Background: The rationales of current research assessed postoperative complications in subjects undergo maxillofacial surgery underneath general anesthesia plus decide the shelter of general anesthesia with co morbidities. Subjects and Methods: Current research includes 250 subjects who were operated underneath general anesthesia. Different parameters such as age, gender, laboratory and radiographic parameters, preoperative intraoperative, and postoperative were documented. Post-operative problems were evidenced and separated: 1. Complications unswervingly connected to surgical process 2. Complications connected to general anesthesia. Results: There were 140 males and 110 were females. About 79% of subjects demonstrate sore throat, nausea in 68%, vomiting in 43%, headache in 31%, hypertension in 19%, hypotension in 30%, myalgias in 22%, bleeding in 3%, sleep trouble with connected behavioral troubles in 33% plus wound infection in 12%.Conclusion: Majority of post-operative impediments was minor and convenient, though several complications are most important and these can be slanted to fundamental systemic condition. General anesthesia is a secure method of guarantee wellbeing and reassure through surgery but still, there can be complications that have to be documented.